Sequential Immunization With Live-Attenuated Chimeric Hemagglutinin-Based Vaccines Confers Heterosubtypic Immunity Against Influenza A Viruses in a Preclinical Ferret Model - Liu, Wen-Chun; Nachbagauer, Raffael; Stadlbauer, Daniel; Solórzano, Alicia; Berlanda-Scorza, Francesco; García-Sastre, Adolfo; Palese, Peter; Krammer, Florian; Albrecht, Randy A. (Frontiers in Immunology, 2019)
Due to continuous antigenic drift and occasional antigenic shift, influenza viruses escape from human adaptive immunity resulting in significant morbidity and mortality in humans. Therefore, to avoid the need for annual reformulation and readministration of seasonal influenza virus vaccines, we are developing a novel chimeric hemagglutinin (cHA)-based universal influenza virus vaccine, which is comprised of sequential immunization with antigens containing a conserved stalk domain derived from a circulating pandemic H1N1 strain in combination with “exotic” head domains. Here, we show that this prime-boost sequential immunization strategy redirects antibody responses toward the conserved stalk region. We compared the vaccine efficacy elicited by distinct vaccination approaches in the preclinical ferret model of influenza. All ferrets immunized with cHA-based vaccines developed stalk-specific and broadly cross-reactive antibody responses. Two consecutive vaccinations with live-attenuated influenza viruses (LAIV-LAIV) conferred superior protection against pH1N1 and H6N1 challenge infection. Sequential immunization with LAIV followed by inactivated influenza vaccine (LAIV-IIV regimen) also induced robust antibody responses. Importantly, the LAIV-LAIV immunization regimen also induced HA stalk-specific CD4+IFN-+ and CD8+IFN-+ effector T cell responses in peripheral blood that were recalled by pH1N1 viral challenge. The findings from this preclinical study suggest that an LAIV-LAIV vaccination regimen would be more efficient in providing broadly protective immunity against influenza virus infection as compared to other approaches tested here.